Constraints on the shallow deformation around the Main Frontal Thrust in central Nepal from refraction velocities - Liu, Yixiang (2020)
The youngest fault system in the Himalayan orogeny is the Main Frontal Thrust (MFT), the frontal ramp of theMain Himalayan Thrust, which is expected to host the largest and most damaging earthquakes in Nepal. Wecharacterize the upper few hundred meters below the surface across two MFT fault strands using ten high-resolution seismic profiles that we acquired in 2014 and 2015 with a 6-tonne Vibroseis source. We use firstarrival picks from 625,416 seismic traces to derive P-wave seismic velocity models using a wavepath eikonaltraveltime inversion method, and derive estimates of alluvium thickness and water table depth across thesefaults (the Patu and Bardibas thrusts), allowing us to constrain the subsurface geometry of the MFT.Our results show that 1) seismic velocities range from 255 to 3660 m/s, consistent with dry and saturatedalluvium, and Siwalik bedrock; 2) low-velocity alluvium varies between ~20–50 and ~80–120 m thick in thehanging wall and footwall of the Bardibas thrust, respectively, corresponding to ~60–70 m of uplift of thehanging wall since deposition; 3) the two thrusts are soft-linked, and the western tip of the Bardibas thrust lies~6 km west of its surface expression; 4) during the dry season, the water table is ~25–100 m higher in thehanging walls of the faults than in their footwalls, due to the larger thickness of permeable alluvium in thefootwalls, and the water table shallows towards the east in the hanging wall of the Bardibas thrust; and 5)consistent with previous studies, the Patu thrust breaches the surface, while the Bardibas thrust is blind at RatuKhola. These results also demonstrate that it should be possible to constrain the rate of uplift above the Bardibasthrust by drilling and dating sediments on both sides, which would complement existing measurements fromterrace uplift.